Parallel robot for 3D additive manufacturing - Liau, Yee Xiang (2016)
Fused Deposition Modelling (FDM) 3D printing technology was integrated with a 6 degree of freedom (DOF) delta robot to form the prototype for this project. It is an improvement from conventional 3-DOF FDM 3D printer which were constructed based on 3 axes (x, y and z) configuration that limit the printing process. On the flip side, parallel robot such as delta robot are reputable for high speed maneuverability and the degree of freedom in its motion path. These would significantly improve the process capability and the flexibility in the motion path of the print head during the printing process. One of the core objective for this project was to resolve parallelism issue that arose in this prototype. Another objective was to calibrate the extruder and obtain parameters that would give best printing. The focus of this report would be on delta robot motion controls, extrusion calibration and design of experiment to obtain ideal parameters. Kinematics equations were used to implement velocity control through changing the kinematic variables of the joints. These kinematics variables changes with respect to time to allow proper coordination among the 6 axes in the prototype. With synchronous coordination between these axes, parallel motion at the end effector of the prototype was achieved. Effectiveness of this changes in the controls were proved by conducting linearity test to draw shapes on a piece of paper with a pen attached at the end effector. Faults found in the extrusion process were resolved by identifying the root causes and making necessary component replacement. In-depth studies for the extrusion process were conducted and analyzed during troubleshooting of these faults. The effect of the extrusion flow rate and temperature on the printing quality and productivity was investigated by 2K design experiment. It was found that the best setting is achieved with extrusion flow rate of 4900 mm/min at 230ºC.